Patient empowerment: The need to consider it as a measurable patient-reported outcome for chronic conditions - McAllister Marion; Dunn Graham; Payne Katherine; Davies Linda; Todd Chris (BMC, 2012)
Abstract Background Health policy in the UK and elsewhere is prioritising patient empowerment and patient evaluations of healthcare. Patient reported outcome measures now take centre-stage in implementing strategies to increase patient empowerment. This article argues for consideration of patient empowerment itself as a directly measurable patient reported outcome for chronic conditions, highlights some issues in adopting this approach, and outlines a research agenda to enable healthcare evaluation on the basis of patient empowerment. Discussion Patient empowerment is not a well-defined construct. A range of condition-specific and generic patient empowerment questionnaires have been developed; each captures a different construct e.g. personal control, self-efficacy/self-mastery, and each is informed by a different implicit or explicit theoretical framework. This makes it currently problematic to conduct comparative evaluations of healthcare services on the basis of patient empowerment. A case study (clinical genetics) is used to (1) illustrate that patient empowerment can be a valued healthcare outcome, even if patients do not obtain health status benefits, (2) provide a rationale for conducting work necessary to tighten up the patient empowerment construct (3) provide an exemplar to inform design of interventions to increase patient empowerment in chronic disease. Such initiatives could be evaluated on the basis of measurable changes in patient empowerment, if the construct were properly operationalised as a patient reported outcome measure. To facilitate this, research is needed to develop an appropriate and widely applicable generic theoretical framework of patient empowerment to inform (re)development of a generic measure. This research should include developing consensus between patients, clinicians and policymakers about the content and boundaries of the construct before operationalisation. This article also considers a number of issues for society and for healthcare providers raised by adopting the patient empowerment paradigm. Summary Healthcare policy is driving the need to consider patient empowerment as a measurable patient outcome from healthcare services. Research is needed to (1) tighten up the construct (2) develop consensus about what is important to include (3) (re)develop a generic measure of patient empowerment for use in evaluating healthcare (4) understand if/how people make trade-offs between empowerment and gain in health status.